Ndox-Glint - Calame-Levert, Florence; Chaizemartin, Julie 1984- (Templon, 2024)
Alioune Diagne. Ndox-Glint was published on the occasion of Alioune Diagne’s solo exhibition at the Musée des Beaux-Arts de Rouen. As part of the "La Ronde" contemporary art festival, Alioune Diagne showcases Ndox-Glint, a new series of 11 paintings placed in dialogue with the Museum’s Impressionist Masters. Alioune Diagne’s powerfully coloured canvases are inhabited by canoes, fishermen and the shores of Senegal. From his native country, he has always been drawn to the banks of the Senegal and Gambia rivers, capturing the liveliness and energy of the scenes of life he observes
Impressum: This catalogue has been published on the occasion of Alioune Diagne's exhibition "Ndox-Glint" at Musée des Beaux-Arts de Rouen, from September 15, 2023 to March 5, 2024 as part of the contemporary art festival "La Ronde"
Keywords: Diagne, Alioune / Exhibitions; Diagne, Alioune -- 1985-; Ausstellungskatalog -- Musée des Beaux-Arts de Rouen -- 15.09.2023-05.03.2024 -- Rouen; Bildband